PENERAPAN TEKNOLOGI TEPAT GUNA BERUPA ALAT PENGUSIR HAMA BURUNG OTOMATIS DI DESA MALAJU - Andriani, Titi; Esabella, Shinta (Jurnal Pengabdian Rekayasa Sistem, 2023)
As an academic, a lecturer's primary responsibilities include performing community service in addition to their teaching and research responsibilities. Teaching and research responsibilities is a way for academics to use and share research and study findings with the community in an effort to empower and enhance the standard of living there. 3,556 people live in Malaju Village, one of the communities in Kilo District, Dompu Regency, and farming is their primary source of income. Farmers frequently run into issues when the rice harvest approaches, specifically the presence of avian pests. Rice yields are typically decreased by bird consumption of the seeds. Appropriate Technology for automatic bird repellents is a device that generates sound waves with adjustable frequency values and can produce falcon sounds, assuming that falcons are natural predators of other birds. Through its implementation, this TTG is anticipated to assist the neighborhood in increasing rice yields through its duties in research and education.